(untitled) (Scientific journal of the Fergana State University, 2024)
Fruit growing is a complex and multifaceted branch of agriculture. Fruits are a source of sugar, organic acids, proteins, fats, flavoring substances, pectin, aromatic substances, colloids, mineral salts, enzymes and vitamins necessary for the human body. The sweetness of the fruit helps to digest food well. Many fruits have healing properties, preserve and strengthen the body’s defenses. Among them, pears are very useful, second only to apples. Pear orchards are grown in various soil, climatic and agrotechnical conditions, and their fruits are used fresh, dried and processed for various purposes. Measures have been developed to protect pear orchards from pests, and special importance is attached to their implementation locally. Because the implementation of these measures ensures a balance between the needs of the population for consumption of pear products, the demand of processing enterprises and the requirements for the production of products for export, as well as the offers of product manufacturers. The pear worm also causes damage to the leaves and young shoots of the pear, which leads to a decrease in yield.